Implementation Of Regional Regulation No. 4/2009 On Ohoi Leadership Elections In Southeast Maluku - Ars Kassiuw, Venansius Yohanis; Nurcholis, Chanif; Zacharias, Tehubijuluw (JIAP (Jurnal Ilmu Administrasi Publik), 2026)
Abstract This research is an analytical descriptive research with a qualitative approach that aims to identify and map problems that hinder the implementation of Regional Regulation No. 4 of 2009 concerning Procedures for Nomination, Election and Inauguration of the Head of Government of Ohoi in Southeast Maluku. This study uses primary data and secondary data. Primary data was obtained from observations, documentation and in-depth interviews with 15 selected informants. The analysis method used is a qualitative method with a socio-legal approach consisting of a conditional approach, statute approach and legal policy Conditional approach refers to the policy strategy of the Ohoi government regulation in Southeast Maluku Regency related to the mechanism for electing the head of government of Ohoi. Statute approach refers to the legislative approach related to Villages and Customary Villages; and legal policy refers to government policies in terms of the implementation of Regional Regulation No. 4 of 2009.The research found that in the implementation of the policy of Regional Regulation No. 4 of 2009, factors that hinder implementation include 1) unclear parameters of hereditary rights in the nomination of ohoi heads, (2) government intervention through BSO and regional officials in the realm of customary authority, and (3) inconsistency in the implementation of Regional Regulation. These problems cause horizontal and vertical conflicts with the Regional Government. The harmonization of customary law and state law as a mandate of the 1945 Constitution Article 18 manifested in Law No. 6 of 2014 concerning Villages is a new hope for customary villages to show their existence. The adaptation of customary law and state law is a necessity as an effort to strengthen the foundation of legitimate, effective, and sustainable customary government in Southeast Maluku.